Excitability of Rat Superficial Dorsal Horn Neurons Following a Neonatal Immune Challenge - Tadros, Melissa A.; Zouikr, Ihssane; Hodgson, Deborah M.; Callister, Robert J. (Frontiers in Neurology, 2018)
Previous studies have shown that neonatal exposure to a mild inflammatory challenge, such as lipopolysaccharide (LPS, Salmonella enteriditis) results in altered pain behaviors later in life. To further characterize the impact of a neonatal immune challenge on pain processing, we examined the excitability of superficial dorsal horn (SDH) neurons following neonatal LPS exposure and subsequent responses to noxious stimulation at three time-points during early postnatal development. Wistar rats were injected with LPS (0.05 mg/kg i.p.) or saline on postnatal days (PNDs) 3 and 5, and later subjected to the formalin test at PNDs 7, 13, and 22. One hour after formalin injection into the plantar hindpaw, animals were euthanized (Ketamine, 100 mg/kg i.p.) and transverse slices from the lumbosacral spinal cord were prepared. Whole-cell patch-clamp recordings were made from SDH neurons (KCH3SO4-based internal, 22–24°C) on the ipsi- and contralateral sides of the spinal cord. Depolarising current steps were injected into SDH neurons to categorize action potential (AP) discharge. In both saline- and LPS-treated rats we observed age-related increases the percentage of neurons exhibiting tonic-firing, with concurrent decreases in single-spiking, between PND 7 and 22. In contrast, neonatal exposure to LPS failed to alter the proportions of AP discharge patterns at any age examined. We also assessed the subthreshold currents that determine AP discharge in SDH neurons. The rapid outward potassium current, IAr decreased in prevalence with age, but was susceptible to neonatal LPS exposure. Peak IAr current amplitude was greater in ipsilateral vs. contralateral SDH neurons from LPS-treated rats. Spontaneous excitatory synaptic currents (sEPSCs) were recorded to assess network excitability. Age-related increases were observed in sEPSC frequency and time course, but not peak amplitude, in both saline- and LPS-treated rats. Furthermore, sEPSC frequency was higher in ipsilateral vs. contralateral SDH neurons in LPS-treated animals. Taken together, these data suggest a neonatal immune challenge does not markedly affect the intrinsic properties of SDH neurons, however, it can increase the excitability of local spinal cord networks via altering the properties of rapid A-type currents and excitatory synaptic connections. These changes, made in neurons within spinal cord pain circuits, have the capacity to alter nociceptive signaling in the ascending pain pathway.